1994
DOI: 10.2135/cropsci1994.0011183x003400030027x
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Level of Nitrogen Fertility Effects on Spring Wheat Yield in Eastern Canada

Abstract: Bread wheat (Triticum aestivum L.) produced in areas of higher rainfall, such as eastern Canada, are often low in protein. Our objective was to determine if N management could be used as a way to produce bread quality wheat in eastern Canada. An experiment was conducted for 2 yr at two Quebec sites. The effects of N fertilizer level and timing on grain yield, yield components, and lodging level of four hard red spring wheat cultivars with breadmaking potential were investigated. The soil type was Ste‐Rosalie c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
51
1
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 0 publications
11
51
1
2
Order By: Relevance
“…The greater precipitation during the 1994 growing season was probably responsible for the greater amount of N fertilizer required for wheat. Our findings in 1994 are supported by the results of Ayoub et al (1994a), as in their study the N rate required to reach the maximum yield of four cultivars of spring wheat in eastern Canada was around 120 kg N ha -1 .…”
Section: Grain Yield and N Uptakesupporting
confidence: 86%
See 1 more Smart Citation
“…The greater precipitation during the 1994 growing season was probably responsible for the greater amount of N fertilizer required for wheat. Our findings in 1994 are supported by the results of Ayoub et al (1994a), as in their study the N rate required to reach the maximum yield of four cultivars of spring wheat in eastern Canada was around 120 kg N ha -1 .…”
Section: Grain Yield and N Uptakesupporting
confidence: 86%
“…The wheat yield response to N fertilizer varies with the climatic conditions and soil N supplying power during the growing season (Giroux and Tran 1989;Carr et al 1992) and with cultivar (Ayoub et al 1994a;Tremblay and Vasseur 1994). A significant increase in grain yield has been observed with N fertilization especially when soil N supply was low, but application of very high N rate can reduce grain yield by increasing lodging and disease incidence (Sinclair and Dewit 1975).…”
Section: Mots Clésmentioning
confidence: 99%
“…However, other spring wheat research in Que´bec has shown that the addition of N increased test weight in half of the sites studied (Ayoub et al 1994). In our study, the added fertility may have encouraged weed competition and reduced resources available to the crop during grain filling, resulting in lower test weight.…”
Section: Wheat Qualitymentioning
confidence: 77%
“…Such response can be attributed to the adequate nitrogen availability which might facilitate the tillering ability of the plants, resulting in a greater spike population. Ayoub et al(1994) also reported that spike population increased with increase in nitrogen level. Table 4 data show that there were no significant differences in spikes weight of the four wheat cultivars.…”
Section: Plant Population Per Meter Squarementioning
confidence: 88%
“…Nitrogen comprises 7% of total dry matter of plants and is a constituent of many fundamental cell components such as nucleic acids, amino acids, en-zymes, and photosynthetic pigments (Bungard et al, 1999). Ayoub et al(1994) reported that spilt N application had little effect on yield, but decreased lodging and spike population, while grain weight increased. Nitrogen application at 120 kg/ha for wheat has been recommended by various research workers (Lathwal et al, 1992;Das et al, 1993).…”
Section: Introductionmentioning
confidence: 99%